ZEOLITE A FROM COAL POWER PLANT FLY ASH: SYNTHESIS AND ADSORPTIVITY TEST - Naibaho, Twinca
Coal as fuel of power plants will remain utilized for long time period. A commercial and mature technology in power plants is coal combustion which produces fly ash. Discharged fly ash from such power plants containts fruitful minerals, i.e. alumina and silica. Fly ash is processed to reduce emission from coal combustion. One of very prospective products from fly ash is zeolite. This study aims to prepare zeolite A from coal fly ash. This research is conducted in a couple of stages, namely pretreatment and synthesis stage. The pretreatment is calcination of coal fly ash at 850oC for 2 hours followed by hydrochloric acid (HCl) washing at 80 oC for 1 hour and aqua dm washing at 60 oC for 1 hour twice. The synthesis is carried out by fusion-alkaline hydrothermal method. The fusion stage is accomplished by adding NaOH then calcinated at 550 oC for 2 hours. Aging process is carried out in shaker incubator. Then, hydrothermal process is carried out at 80 oC for 6 and 12 hours. The variations are put on Na compound, ratio of fly ash to Na compound, and ratio of Si/Al. Zeolite A is characterized using XRD, SEM, and SAA instruments. Adsorptivity test is conducted on zeolites by AAS method. This study shows that pretreatment alters the morphology and reduces the impurities content of fly ash, such as CaO from 12.20% to 6.29%, MgO from 6.69% to 3.26%, and Na2O from 4.21% to 1.51%. This research succeeded in synthesizing zeolite A and zeolite LTA. The crystallinity of the obtained zeolites ranges from 11% to 79%, and their surface area ranges from 3 to 69 m2/g. The increase of NaOH to fly ash ratio to 1.6 generally raises selectivity and crystallinity of the zeolite. The increase of Si to Al ratio raises its crystallinity to the optimum ratio then a decrease occurs. The addition of crystallisation time generally makes the crystallinity of the product obtained higher. The minimum zeolite adsorption capacity for metal ion Cu2+, Zn2+, dan Ni2+ is 38,02; 43,98; dan 49,55 mg/g in order.